Carbapenem-resistant Pseudomonas aeruginosa and carbapenem use in Japan: an ecological study. Issue 10 (October 2019) - Terahara, Fumitaka; Nishiura, Hiroshi
Objective: This study focused on carbapenem resistance in Pseudomonas aeruginosa and examined potential ecological correlations with carbapenem use in Japan. Methods: The proportion of carbapenem-resistant P. aeruginosa isolates from 2015 and 2016 by prefecture was obtained from the Japan Nosocomial Infections Surveillance system. Data on carbapenem use was obtained from the National Database of Health Insurance Claims. The correlation between the proportion of carbapenem-resistant isolates and carbapenem consumption was assessed in a cross-sectional manner. The study also collected information on other variables including the numbers of physicians, nurses and medical facilities per 100 000 individuals by prefecture. Results: Both the proportion of carbapenem-resistant P. aeruginosa isolates and levels of carbapenem use were higher in western Japan. Using a multivariate model, only carbapenem use remained significantly associated with the proportion of carbapenem-resistant isolates. Conclusions: Carbapenem use and the proportion of carbapenem-resistant P. aeruginosa isolates were positively correlated. By longitudinal data collection, this approach offers an avenue to establish causal links as the frequency of carbapenem-resistant P. aeruginosa isolates starts to change in the future.